Calcined clays for sustainable concrete proceedings of the 1st International Conference on Calcined Clays for Sustainable Concrete - International Conference on Calcined Clays for Sustainable Concrete Zurich, Switzerland) 2015; Scrivener, Karen; Favier, Aurelie; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2015)
This volume focuses on research and practical issues linked to Calcined Clays for Sustainable Concrete. The main subjects are geology of clays, hydration and performance of blended systems with calcined clays, alkali activated binders, economic and environmental impacts of the use of calcined clays in cement based materials. Topics addressed in this book include the influence of processing on reactivity of calcined clays, influence of clay mineralogy on reactivity, geology of clay deposits, Portland-calcined clay systems, hydration, durability, performance, Portland-calcined clay-limestone systems, hydration, durability, performance, calcined clay-alkali systems, life cycle analysis, economics and environmental impact of use of calcined clays in cement and concrete, and field applications. This book compiles the different contributions of the 1st International Conference on Calcined Clays for Sustainable Concrete, which took place in Lausanne, Switzerland, June, 23-25, 2015.The papers present the latest research in their fields. It contains nearly 80 papers and abstracts. Overall, this work gives a broad view of research on calcined clays in the field of construction and will stimulate further research into calcined clays for sustainable concrete.
Electronic reproduction.
Keywords: Cement -- Congresses; Sustainable engineering -- Materials -- Congresses; Clay -- Congresses; Concrete -- Congresses; Electronic books